A KEYWORD CO-OCCURRENCE ANALYSIS OF RESEARCH ON SPIRITUALITY FROM AN ISLAMIC PERSPECTIVE BETWEEN 2018 TO 2022: EMERGING RESEARCH TRENDS - Bidayah Zulkepli; Qarem Mohamed Mustafa; Fathiyyatunnur Idris; Siti Nursadrina Mohd Isa; Wan Nurul Afiqah Akmal W.M. Affandi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The article provides a detailed overview of the extant literature on spirituality from Islamic perspectives as well as it reveals the trends and suggests future research directions for scholars who wish to contribute to this rapidly growing field. A bibliometric analysis was conducted using data obtained from the Scopus database by searching articles, book chapters, and manuscripts containing the term “spirituality” AND “Islamic perspectives” OR “views” OR “concept” on their titles, abstracts, and/or keywords. Publish or Perish, and VOSviewer software were then used to obtain publication trends, citation index per year, highly cited articles, and keyword co-occurrence network. There is a fluctuating trend of publication on spirituality from an Islamic perspective such that a decrease occurred in 2021 compared to the years prior. Although 2018 has the highest total citations (n=351) and average citations per article (5.40), 2021 has the highest number of cited publications (n=116) which suggest a notable presence of influential works in the year 2021. Some of the themes with the highest keyword co-occurrence are well-being (27 items), clinical studies (26 items), Islamic thoughts and civilization (13 items), and medical ethics (5 items). There are abundant articles published within the year 2018 to 2022 regarding spirituality from an Islamic perspective and the bibliometric analysis found emerging trends specifically on themes of well-being, clinical studies, and Islamic thoughts and civilization which future researchers can focus on.